Dependence of the L-Mode scrape-off layer power fall-off length on the upper triangularity in TCV. (6th March 2018) - Faitsch, M; Maurizio, R; Gallo, A; Coda, S; Eich, T; Labit, B; Merle, A; Reimerdes, H; Sieglin, B; Theiler, C
Abstract: This paper reports on experimental observations on TCV with a scan in upper triangularity δ up, including negative triangularity, focusing on the power fall-off length λ q in L-Mode. The upper triangularity is scanned from −0.28 to 0.47. Smaller λ q out is measured at the outer divertor target for decreasing δ up together with higher edge temperature T e, edge leading to increased confinement. This effect is observed for both magnetic drift directions for discharges in deuterium and helium. In helium larger λ q values are observed compared to deuterium. The power fall-off length at the inner divertor target λ q in has a non-monotonic behaviour with changing triangularity. The largest values are around δ up = 0 . The ratio λ q in / λ q out increases for decreasing δ up for positive triangularity and is approximately constant for negative triangularity. λ q out is compared to available scaling laws. Partial agreement is only observed for a scaling law containing a proxy for T e, edge at ASDEX Upgrade (Sieglin 2016 Plasma Phys. Control. Fusion 58 055015). Extending this scaling to TCV and using T e, edge at ρ pol = 0.95 suggests that λ q out is independent of machine size λ q L - Mode ( mm ) = 165 · B pol ( T ) − 0.66 · A ( u ) − 0.15 · T e, edge ( eV ) − 0.93 · R ( m ) − 0.03 . Possible explanations for smaller λ q out for decreasing δ up is a reduction in turbulence or a direct effect of increasing T e, edge .